A novel approach for navigational safety evaluation of inland waterway ships under uncertain environment. Issue 1 (30th March 2022) - Liu, Jia; Jiang, Xinchen; Huang, Weina; He, Yankang; Yang, Zhisen
Abstract: This paper proposes a safety evaluation model of inland waterway ship navigation based on the fuzzy theory and evidential reasoning (ER) approach. The proposed model is a three-level hierarchical system consisting of 18 indicators that are identified and determined through literature review and expert surveys. By using fuzzy theory, the factors of the index level are converted into belief distributions, and the information of indicators within each level is merged by using the ER approach so that the evaluation of the ship's navigation safety can be realized. This model can deal with multi-source information and both qualitative and quantitative indicators in an integrated framework. Some case studies on the safety status of ships navigating in the middle reaches of the Yangtze River during dry season are conducted to validate the feasibility and practicability of the proposed model. The results show that the risk levels obtained from the proposed model are consistent with the real-life situation to a large extent. The novel model proposed in this study provides a useful reference for maritime safety management and will help managers and decision-makers in the risk prevention and early warning of inland waterway transportation accidents.